KINERJA KOPERASI PERIKANAN PANTAI MADANI DARI SISI KEUANGAN (Kasus Koperasi di Teluk Pambang, Bengkalis) - M Ramli; Nur’aini ' (Berkala Perikanan Terubuk, 2009)
Research aims to see cooperation performance from finance, Is theperformance good and Well. Based on finance ratio analysis, Cooperationliquidity value on standard value 125%, Also solvability value on standard value110%. For value rentability value under standard value 10%, Meaning fromcooperation performance rentability aspect not good. Based on heavy value,LSR's value total with heavy still on 100%, Meaning Koperasi Perikanan PantaiMadani (KPPM) still stay in condition wells.